HUBUNGAN DISKUSI KELOMPOK DENGAN KEMAMPUAN BERBICARA SISWA KELAS V MI MA’ARIF KALIBEBER - Amelia Khodijah; Nashokah; Chairani Astina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Speaking ability is one of the language skills that needs to be developed in elementary school students, yet observations show that many students remain passive and lack confidence in expressing opinions during Indonesian language lessons. While group discussion is widely recommended to address this problem, studies that statistically measure the strength of its relationship with speaking ability at the madrasah ibtidaiyah level remain limited. This study aimed to determine the relationship between group discussion and students’ speaking ability in the fifth-grade Indonesian language subject at MI Ma’arif Kalibeber Mojotengah during the 2025/2026 academic year. This study employed a quantitative approach with a correlational design, involving 25 fifth-grade students selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire, an oral speaking test, observation, and documentation, and were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Spearman Rank correlation test. The findings indicate that the group discussion variable obtained a mean score of 64.56 (good category), while speaking ability obtained a mean score of 16.12 (good category); the Spearman Rank correlation test produced a coefficient of 0.983 with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ accepted. These findings contribute to the development of cooperative learning theory in language education and extend current understanding of how peer interaction fosters oral communication skills among elementary students. The conclusion emphasizes the importance of structured group discussion activities in strengthening students’ courage, fluency, and confidence in speaking. The implications of this study include theoretical contributions to the literature on cooperative learning and speaking skill development, and practical implications for teachers and madrasah in designing discussion-based learning activities to improve students’ oral communication. This study also provides opportunities for further research involving larger samples and broader school contexts.